RESEARCH WORK AS A MEANS OF FORMING A SUCCESSFUL PERSONALITY OF A MUSIC TEACHER (Pedagogy of Higher and Secondary Education, 2011)
In article on the basis of studying a theoretical and practical material the maintenance and the basic characteristics of research activity of students reveals, its role proves in formation of the person of the teacher music.
Keywords: research activity; the teacher of music; instrumental performing preparation